Formulating a Policy for Developing Regional Solid Waste Final Disposal Installation in East Java Province - Hitapriya Suprayitno; Bieby Voijant Tangahu (Jurnal Manajemen Aset Infrastruktur & Fasilitas, 2018)
Solid Waste Final Disposal Installation is capital for urban area. Meanwhile,cities, in general, do not have enough space to build Final Disposal Installation. Theyneed to collaborate with the neighboring district. Such collaboration does not alwaysrun well. Therefore, provincial government needs to participate in it by developingRegional Final Disposal Installation to be used together. A policy, for developing this,need to be formulated. A special method, Step by Step Highest Solution Reduction byNeeds and Constraints, has been used to formulate the policy. The main policyformulation for developing Regional Solid Waste Final Disposal Installation consists ofseveral following lines : to develop Regional Final Disposal Installation for all citiesstep by step in function of the city needs; to develop incineration type final disposal stepby step in function on the financial disponibility; to push the rich cities to develop solidwaste incineration step by step; to push implementation of 3R techniques starting fromintermediate disposal installation step by step; to forbid the utilization of open truck fortransporting domestic solid waste from intermediate disposal to final disposal step bystep; to maintain the existing city sanitary landfill final disposal and transforming it intoincineration installation step by step; to promote facilitiies installation made byIndonesian industry, to develop a good institutional arrangement for the Regional FinalDisposal Installation.